Morphological Typology: A Comparative Study of Some Selected Languages - Fadhil Jameel, Abdulkareem; Farhood Khudheyier AlA'amiri, Bushra (Journal of College of Education, 2019)
Morphology is a main part of English linguistics which  deals with forms of words. Morphological typology organizes languages on the basis of these word forms. This organization of languages depends on structural features to mould morphological, patterns, typologising languages, assigning them to analytic, or synthetic types on the base of words segmentability and invariance, or measuring the number of morphemes per word. Morphological typology studies the universals in languages,  the differences and similarities between languages in the structural patterns found in different languages, which occur within a restricted range. This paper aims at distinguishing the various types of several universal languages and comparing them with English. The comparison of languages are set according to the number of morphemes, the degree of being analytic ,or synthetic languages by given examples of each type. Accordingly, it is  hypothesed that languages are  either to be analytic, or synthetic according to the syntactic and morphological form  of  morphemes and their meaning relation. The analytical procedures consist of expressing the morphological types with some selected examples, then making the comparison between  each type and English. The conclusions reached at to the point of the existence of similarity between these morphological types .  English is Analytic , but it has some synythetic aspects, so it validated the first hypothesis and not entirely refuted the second one.
Keywords: Morphological typology, Linguistics, morphemes, Analytic, Synthetic